2014
DOI: 10.1002/mrd.22297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seminal plasma and the presence of a conceptus on regulation of lymphocyte‐cytokine network in porcine endometrium

Abstract: Infusion of seminal plasma in the uterus is known to elicit an instant inflammatory response in the porcine uterus, but whether or not it prepares a uterine immunological response to the presence of conceptuses is not well understood. Seminal plasma induced long-term modulatory effects and conceptus-induced immune changes in leukocyte populations were measured by flow cytometry and mRNAs for various cytokines by quantitative reverse-transcriptase PCR in porcine endometrium collected on Days 6 and 13 from cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…($fourfold dilution) used for artificial insemination in this study most likely would not have any long-term effect on the endometrial proteome on Day 12 of pregnancy (Jalali et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…($fourfold dilution) used for artificial insemination in this study most likely would not have any long-term effect on the endometrial proteome on Day 12 of pregnancy (Jalali et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…The aim of the present study was to gain insight into changes in protein abundance in cycling or pregnant Day‐12 porcine endometria to elucidate how presence of conceptuses might influence the endometrial proteome. Both conceptus‐secreted factors and seminal plasma constituents might influence the endometrial proteome (O'Leary et al, ; Chen et al, ), but the diluted seminal plasma (∼fourfold dilution) used for artificial insemination in this study most likely would not have any long‐term effect on the endometrial proteome on Day 12 of pregnancy (Jalali et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…48 However, the current results show that the boar SP contains cytokines with pro-and anti-inflammatory properties, which confirms the dual SP effect above described for in human and mice, would also appear in sows. Such effect was partially demonstrated by Jalali et al (2014) who asserted that the SP produces an increase in Treg-immune cells and a decrease in expression of inflammatory cytokines in the sow endometrium. 49 The current study also provides clear evidence of differences among boars in both presence and concentration of some cytokines.…”
Section: Discussionmentioning
confidence: 97%
“…Such effect was partially demonstrated by Jalali et al (2014) who asserted that the SP produces an increase in Treg-immune cells and a decrease in expression of inflammatory cytokines in the sow endometrium. 49 The current study also provides clear evidence of differences among boars in both presence and concentration of some cytokines. Differences in concentration were expected because it is well known that SP composition differs quantitatively and qualita-tively among boars, probably genomically driven.…”
Section: Discussionmentioning
confidence: 97%
“…Tolerogenic dendritic cells interact with T cells either locally or within uterine‐draining lymph nodes to expand populations of Treg cells reacting with paternal antigens that, in turn, are recruited via the peripheral circulation into the uterine endometrium (Moldenhauer et al, ; Robertson SA, Guerin LR, Bromfield et al, ) (Figure ). A recent study reported that more Treg cells are present in the endometrium of gilts after seminal fluid infusion, suggesting similar pathways may operate in pigs (Jalali, Kitewska, Wasielak, Bodek, & Bogacki, ). Studies in mice and golden hamsters suggest the effects of seminal fluid ultimately impact the phenotype and health of offspring, as offspring sired by seminal vesicle‐deficient fathers exhibit metabolic dysfunction and elevated anxiety disorder (Bromfield et al, ; Wong et al, ).…”
Section: Seminal Fluid and Generation Of Pregnancy Tolerancementioning
confidence: 92%